PERILAKU BIROKRASI PEMERINTAH DALAM PELAYANAN DI KANTOR CAMAT BIRINGKANAYA KOTA MAKASSAR - Sakir, Ahmad Rosandi (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research explores the behavior of bureaucracy at the Biringkanaya Subdistrict Office, Makassar City, and its impact on administrative services. Focusing on factors such as leadership, employee competence, recognition, workplace facilities, interaction with the community, and service effectiveness, this study employs a qualitative approach with a case study design. The research involves the Biringkanaya Subdistrict Office to ensure the relevance and accuracy of findings regarding bureaucratic behavior in local-level administrative services. The results indicate that bureaucratic behavior is influenced by leadership values, internal norms, and societal dynamics. Effective leadership can enhance service efficiency, while employee competence shapes service quality. The evaluation of the reward system emphasizes the importance of recognizing employee performance. Adequate workplace facilities and supportive technology also play a role in improving bureaucratic efficiency. Interaction with the community has proven to be a crucial factor in building a positive government image. Employee attitudes, effective communication, and responsiveness to community needs are key determinants of public trust. The evaluation of service effectiveness underscores the importance of recognition, positive interaction, and responsiveness to change. Recommendations are provided to strengthen leadership, develop employee competence, improve the reward system, enhance workplace facilities, increase interaction with the community, and improve responsiveness to change. The implementation of these recommendations is expected to enhance the effectiveness of administrative services at the Biringkanaya Subdistrict Office and contribute to a deeper understanding of the dynamics of bureaucratic behavior in the context of public services.